The Young Stages of the Cannonball Jellyfish (Stomolophus sp. 2) from the Central Gulf of California (Mexico) - Laura Cristina Gómez-Salinas; Juana López-Martínez; André Carrara Morandini (Diversity, 2021)
Exploitation of the cannonball jellyfish (Stomolophus sp. 2) is increasing in Mexico and USA due to successful fisheries associated with seasonal blooms in coastal areas. Previously, it was proposed that such blooms could be identified by recognizing the presence of young stages in the water. In our work, we aim to describe the young stages (ephyra and metaephyra) found in the Las Guásimas lagoon, Sonora, Mexico. The description of specimens is based on photographs, drawings, and morphological measurements aimed at helping in the early detection of blooming events.